Endoscopic incision of protruding right ureterocele in a single collecting system: a case report (Medical Journal of Indonesia, 2016)
Protruding ureterocele is a very rare case found in the literature. We are reporting a 21 year-old female with an intermittent protruding mass from urethra, accompanied by dysuria, hematuria, and recurrent urinary tract infection. Inspection of the external genitalia revealed a protruding mass from the urethra which could be reduced manually. Excretory urography showed bilateral single collecting systems, grade II hydronephrosis of the right kidney, and a cobra head appearance of the lower right pelvis. The patient was diagnosed with a protruding right ureterocele in a single collecting system, and thus, endoscopic incision of a ureterocele was performed. Ultrasonography which was carried out three weeks after the procedure confirmed no residual hydronephrosis or ureterocele in the bladder. Voiding cystourethrography (VCUG) underwent at a three-month-follow up revealed a grade 5 vesico-ureteral reflux (VUR) on the right side. Surgical reimplantation was then considered. In conclusion, endoscopic incision was safe and yielded good result for protruding ureteroceles, but the need for secondary surgery in several conditions should be considered.